Modern diagnostic x-ray sources : technology, manufacturing, reliability - Behling, Rolf (Online access with DDA: Askews (Medicine), 2015)
Modern Diagnostic X-ray Sources: Technology, Manufacturing, Reliability gives an up-to-date summary of X-ray source design for applications in modern diagnostic medical imaging. It lays a sound groundwork for education and advanced training in the physics of X-ray production and X-ray interactions with matter. The book begins with a historical overview of X-ray tube and generator development, including key achievements leading up to the current technological and economic state of the field. The book covers the physics of X-ray generation, including the process of constructing X-ray source devic.